2022
DOI: 10.3390/medicina58050666
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib in Metastatic Papillary Thyroid Carcinoma with BRAF K601E Mutation on Liquid Biopsy: A Case Report and Literature Review

Abstract: Differentiated thyroid cancer (DTC) includes papillary and follicular carcinomas and is the most common type of thyroid cancer. The incidence of this cancer has increased in the last few years, and even if its prognosis is generally good for a subset of patients that does not respond to radioactive iodine (RAI) therapy, the prognosis is much worse: the median overall survival (OS) from discovery of metastasis is 3–5 years and the 10-year survival rate is only 10%. Several mutations, including RAS or RET, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A case report in 2022 described a 77-year-old man with diagnosis of metastatic differentiated thyroid cancer and evidence of presence of mutation of BRAF K601E on liquid biopsy was treated with sorafenib, showing a good response to the treatment. [8] A number of retrospective studies have confirmed the efficacy of Lenvatinib in the real world. Nervo et al [9] retrospectively analyzed the effectiveness of Lenvatinib in 12 patients with RAIR-DTC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A case report in 2022 described a 77-year-old man with diagnosis of metastatic differentiated thyroid cancer and evidence of presence of mutation of BRAF K601E on liquid biopsy was treated with sorafenib, showing a good response to the treatment. [8] A number of retrospective studies have confirmed the efficacy of Lenvatinib in the real world. Nervo et al [9] retrospectively analyzed the effectiveness of Lenvatinib in 12 patients with RAIR-DTC.…”
Section: Discussionmentioning
confidence: 96%
“…A case report in 2022 described a 77-year-old man with diagnosis of metastatic differentiated thyroid cancer and evidence of presence of mutation of BRAF K601E on liquid biopsy was treated with sorafenib, showing a good response to the treatment. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%